Dung for dinner : a stomach-churning look at the animal poop, pee, vomit, and secretions that people have eaten (and often still do!) - Virnig, Christine (GodwinBooks/Henry Holt and Company, 2020)
A deliciously disgusting introduction to some of the grossest things we humans put in our mouths--often without even realizing it! From Roman charioteers scarfing wild boar dung to astronauts guzzling their own pee in space to today's kids spreading insect vomit on their toast, this humorous compendium is chock-full of history, science, and fascinatingly gross facts. Bug secretions coating your candy corn? Rodent poop in your popcorn? Physicians tasting their patients' pee? It's irresistibly disgusting!